Transcriptome analysis reveals a molecular understanding of nicotinamide and butyrate sodium on meat quality of broilers under high stocking density - Yuqin Wu; Youli Wang; Dafei Yin; Tahir Mahmood; Jianmin Yuan (BMC Genomics, 2020)
Abstract Background In recent years, increased attention has been focused on breast muscle yield and meat quality in poultry production. Supplementation with nicotinamide and butyrate sodium can improve the meat quality of broilers. However, the potential molecular mechanism is not clear yet. This study was designed to investigate the effects of supplementation with a combination of nicotinamide and butyrate sodium on breast muscle transcriptome of broilers under high stocking density. A total of 300 21-d-old Cobb broilers were randomly allocated into 3 groups based on stocking density: low stocking density control group (L; 14 birds/m2), high stocking density control group (H; 18 birds/m2), and high stocking density group provided with a combination of 50 mg/kg nicotinamide and 500 mg/kg butyrate sodium (COMB; 18 birds/m2), raised to 42 days of age. Results The H group significantly increased cooking losses, pH decline and activity of lactate dehydrogenase in breast muscle when compared with the L group. COMB showed a significant decrease in these indices by comparison with the H group (P < 0.05). The transcriptome results showed that key genes involved in glycolysis, proteolysis and immune stress were up-regulated whereas those relating to muscle development, cell adhesion, cell matrix and collagen were down-regulated in the H group as compared to the L group. In contrast, genes related to muscle development, hyaluronic acid, mitochondrial function, and redox pathways were up-regulated while those associated with inflammatory response, acid metabolism, lipid metabolism, and glycolysis pathway were down-regulated in the COMB group when compared with the H group. Conclusions The combination of nicotinamide and butyrate sodium may improve muscle quality by enhancing mitochondrial function and antioxidant capacity, inhibiting inflammatory response and glycolysis, and promoting muscle development and hyaluronic acid synthesis.